Effects of Content Characteristics and Improvement in User Satisfaction on the Reuse of Home Fitness Application - Nam, Moonju; Song, Taegeon; Kim, Dasran; Jang, Kukjin; Kim, Jinsick; Koo, Byeongsoo; Lee, Jooyeoun; Chung, Myoungsug (Sustainability (Switzerland), 2023)
As the global fitness industry rapidly digitalizes, home fitness applications have emerged as a convenient solution for people to exercise anytime, anywhere. This study investigated the mediation effect of exercise satisfaction on the relationship between content characteristics and continuance intention to use home fitness applications. This study provided guidance for developing effective home fitness applications by analyzing which content characteristics can increase the continuance intention to use home fitness applications. The mediation effect of exercise satisfaction on content characteristics and continuance intention to use was examined using a structural equation model analysis, and 330 survey responses from individuals who have used home fitness applications for exercise were analyzed. The results confirmed that the enhancement of the content characteristics exerted a positive effect on exercise satisfaction and continuance intention to use. Additionally, the enhancement of exercise satisfaction characteristics positively affected the continuance intention to use. Further, exercise satisfaction was observed to exert a significant mediating effect on the relationship between the content characteristics and continuance intention to use home fitness applications. These findings suggest that it is essential to devote significant attention to enhancing content characteristics and exercise satisfaction in the development of home fitness applications.
Keywords: content characteristics; continuance intention to use; exercise satisfaction; fitness app; home fitness